How does the grassroots drive just transition? Evidence from an alteration of resettlement sites in China - Gou, Jie; Jiang, Tianhe; Chen, Shaojun; Lu, Yihua (Frontiers in Sustainable Food Systems, 2022)
Dam-induced resettlement is a typical pattern of development-induced displacement and resettlement (DIDR), which concludes involuntariness and leads to injustice practices. Although the justice of resettlement is studied in existing works, few of them notice that the selection of resettlement sites might be holistically an opportunity for just transition, and the performance of this process is not totally a government arrangement. To address this gap, this paper takes the Multi-level Perspective (MLP) as the theoretical framework, and adopts mixed methods to examine a second selection case of resettlement sites for the Wuxikou dam in Jiangxi Province, China. Based on grounded theory, five categories of resettlees' demands for resettlement sites, namely agricultural production (AP), non-agricultural production (NAP), material life (ML), social life (SL), and reception of natural ecology (RNE) are identified. The multiple conjunctural causation between these demands and resettlees' actions for changing initial resettlement sites is analyzed by Qualitative Comparative Analysis (QCA). Four intermediate solutions as well as the core and peripheral conditions are found. Apart from the bottom-up petitions, how the political environment and governmental administration enabled the resettlees' request for altering resettlement sites is illustrated. It is found that, although the government and resettlees with different interests and action logics, the same result is promoted under the national policies, viz, the implementation of changing resettlement sites, process justice and outcome justice are therein realized. Relative policy implications and outlooks on just resettlement practice are remarked.